2003
DOI: 10.1128/mcb.23.16.5825-5835.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism for Wnt Activation of Canonical Signaling through the LRP6 Receptor

Abstract: LDL receptor-related protein 6 (LRP6) is a Wnt coreceptor in the canonical signaling pathway, which plays essential roles in embryonic development. We demonstrate here that wild-type LRP6 forms an inactive dimer through interactions mediated by epidermal growth factor repeat regions within the extracellular domain. A truncated LRP6 comprising its transmembrane and cytoplasmic domains is expressed as a constitutively active monomer whose signaling ability is inhibited by forced dimerization. Conversely, Wnts ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 49 publications
8
135
1
Order By: Relevance
“…Thus, the mechanisms by which LRP5/6 modulates the Wnt signal are complex. It was proposed that, under normal conditions when Wnt ligand and receptors are at the physiological levels, both frizzled and LRP5/6 receptors are required to achieve efficient intracellular coupling to Wnt/b-catenin signaling (Liu et al, 2003). However, under certain pathological conditions such as in malignancy, high levels of LRP5/6 alone might be able to induce Wnt/b-catenin signaling by modulating subcellular b-catenin distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the mechanisms by which LRP5/6 modulates the Wnt signal are complex. It was proposed that, under normal conditions when Wnt ligand and receptors are at the physiological levels, both frizzled and LRP5/6 receptors are required to achieve efficient intracellular coupling to Wnt/b-catenin signaling (Liu et al, 2003). However, under certain pathological conditions such as in malignancy, high levels of LRP5/6 alone might be able to induce Wnt/b-catenin signaling by modulating subcellular b-catenin distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also showed that LRP5 or LRP6 truncated from the amino-terminal ends (i.e. lacking the extracellular domain) are capable of mediating Wnt/b-catenin signaling independent of either a Wnt ligand or frizzled receptor (Mao et al, 2001;Liu et al, 2003;Brennan et al, 2004). Furthermore, it was demonstrated that a PPPSP motif, which is reiterated five times in the LRP6 intracellular domain, is necessary and sufficient to trigger Wnt/b-catenin signaling (Brennan et al, 2004;Tamai et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many cases of intramolecular self-inhibition (autoinhibition) are known (29,30), but examples of intermolecular inhibition by homodimerization have been reported as well (31)(32)(33)(34)(35)(36). Proteolytic cleavage, phosphorylation, ligand binding, and even lightinduced conformational changes represent different possibilities to initiate or abrogate self-inhibition.…”
Section: Homodimerization In Solutionmentioning
confidence: 99%
“…LRP5 and -6 proteins possess a relatively small intracellular domain and a large extracellular domain containing several potential protein interaction domains (He et al, 2004). Truncated proteins that lack the extracellular portion of the protein, but still contain the transmembrane and intracellular domains, produce a constitutively active canonical Wnt signal (Liu et al, 2003). By contrast, LRP proteins lacking only the intracellular domain serve as dominant negative proteins (Tamai et al, 2000).…”
Section: Wnt Receptionmentioning
confidence: 99%